Potential species richness of frogs and diurnal butterflies in three biogeographical units from northeastern Colombia: conservation Implications (2018)
We present an estimation of the potential species richness of frogs, and diurnal butterflies distributed in the departments of Norte de Santander and Santander, Colombia, and analyze the implications for conservation of such high Andean species. From June 2012 to May 2016, we sampled across the Almorzadero, Santurbán and Tamá biogeographical units to gather presence data of 7 anuran species and 29 butterflies species from the superfamily Papilionoidea. We modeled the potential distribution of each species, converted every model to binary, and the sum up of unique species per cell allowed to estimate the model of potential richness, generating the total number of species for every 1 km2 cell. Every model was validated against field data, vegetation cover, and altitude. Our results suggest the existence of species’ concentration zones, specifically in the places of convergence between biogeographical units; it was evident the high levels of data deficiency in some places. Finally, it was clear the importance of these zones as a continuum of biogeographic conditions to maintain the biological diversity.